Sacrospinous Fixation and Vaginal Uterosacral Suspension—Evaluation in Uterine Preservation Surgery. Issue 5 (22nd May 2023) - Woodburn, Katherine L.; Yuan, Angela S.; Torosis, Michele; Roberts, Kasey; Ferrando, Cecile A.; Gutman, Robert E.
Abstract : Importance: Vaginal hysteropexy can be performed via the uterosacral or the sacrospinous ligament(s), but little data exist comparing these routes. Objective: The aim of the study was to compare prolapse recurrence, retreatment, and symptoms along with the incidence of adverse events between patients undergoing vaginal uterosacral hysteropexy and sacrospinous hysteropexy. Study Design: This was a multicenter retrospective cohort study of patients who underwent vaginal uterosacral or sacrospinous hysteropexy (SSHP) between 2015 and 2019. Anatomic failure was the primary outcome, defined as prolapse beyond the hymen. Composite failure was defined as anatomic failure, bulge symptoms, and/or retreatment for prolapse. Results: At 4 geographically diverse referral centers, 147 patients underwent SSHP and 114 underwent uterosacral hysteropexy. The 1-year follow-up rate was 32% (83/261) with no difference between groups. There were 10 (3.8%) anatomic failures: 3 (2%) sacrospinous and 7 (6.1%) uterosacral ( P = 0.109). There was no difference in bulge symptoms (9.9%), composite failure (13%), or median prolapse stage (2). The overall incidence of complications was low (7%; 95% confidence interval, 4.12%–10.43%) with a higher rate of ureteral kinking in the uterosacral group (7% vs 1.4%, P = 0.023). With a median follow-up of 17 months, 4.6% underwent subsequent hysterectomy and 6.5% had treatment for uterine/cervical pathology. Conclusions: One year after hysteropexy, 1 in 3 patients were available for follow-up, and there were no differences in prolapse recurrence between patients who underwent uterosacral hysteropexy versus SSHP. The incidence of adverse events was low, and less than 5% of patients underwent subsequent hysterectomy for prolapse.